Predictive Factors of Depression in Heart Failure Patients - João Ricardo da Costa Monteiro Botto (2021)
Background: Depressive symptomatology in Heart Failure (HF) has gained great importance, affecting one in five patients. This comorbidity is associated with an increased risk for hospitalization and mortality. Therefore, being aware of depression associated factors is key to a better outcome for these patients. The present study aimed to analyse those associated factors, including New York Heart Association (NYHA) functional classes, while also evaluating the presence of depressive symptoms in HF outpatients. Methods: This cross-sectional study is part of a larger research project (Deus Ex-Machina/NORTE-01-0145-FEDER-00026). HF patients were recruited from an outpatient clinic at a University Hospital. Exclusion criteria were: inability to communicate, severe visual/auditory acuity deficit, or NYHA Class IV. Sociodemographic and clinical data, including NYHA classes (I, II, III), were registered. Depression and anxiety were assessed using the Patient Health Questionnaire-9 and the Generalized Anxiety Disorder-7, respectively, having been considered clinically relevant when a score ≥ 10 was obtained. Predictive factors of depression were determined by logistic regression analysis. Results: From 136 HF patients, depression was present in 26%. Female gender, higher NYHA classes, and presence of anxiety were significantly associated with depression. Patients in the NYHA Class III (OR = 8.687; 95% CI: [1.769; 42.652]; p = 0.008) and with anxiety (OR = 17.19; 95% CI: [6.038; 48.934]; p < 0.001) had a higher risk of presenting clinically relevant depression than the ones in the NYHA Class I and without anxiety, respectively. Conclusions: Depression in the HF patients had a considerable rate (fitting previous studies' results), and its predictors were found to be the worst analysed NYHA class and anxiety. Consequently, preventing, monitoring, and treating depression in the management of HF patients becomes crucial. Further research is needed to better understand the association between depression and NYHA classes, towards an eventual improvement of these patients' outcomes.